2021
DOI: 10.1016/j.rinp.2021.104182
|View full text |Cite
|
Sign up to set email alerts
|

A new extension of state-space SIR model to account for Underreporting – An application to the COVID-19 transmission in California and Florida

Abstract: In the absence of sufficient testing capacity for COVID-19, a substantial number of infecteds are expected to remain undetected. Since the undetected cases are not quarantined, they can be expected to transmit the infection at a much higher rate than their quarantined counterparts. That is, in the absence of extensive random testing, the actual prevalence and incidence of the SARS-CoV-2 infection can be significantly higher than that being reported. Thus, it is imperative that the information on the percentage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…However, the above studies directly study the spatiotemporal distribution of COVID-19 through reported case data, ignoring the possible under-reporting of data in reported cases ( Lau et al, 2021 ). The conclusions obtained directly from the reported cases may deviate from the actual situation, thereby affecting the judgment of decision-makers( Bastos et al, 2021 ; Deo & Grover, 2021 ).…”
Section: Related Workmentioning
confidence: 99%
“…However, the above studies directly study the spatiotemporal distribution of COVID-19 through reported case data, ignoring the possible under-reporting of data in reported cases ( Lau et al, 2021 ). The conclusions obtained directly from the reported cases may deviate from the actual situation, thereby affecting the judgment of decision-makers( Bastos et al, 2021 ; Deo & Grover, 2021 ).…”
Section: Related Workmentioning
confidence: 99%
“…Wu et al, 2020 [22] reported that the actual number of infections was estimated to be 3 to 20 times higher than the confirmed cases for various states of the United States of America. Lu et al, 2020 [23] showed that there were drastic cases of underreporting in many countries worldwide.…”
Section: Parameters Of the Modelmentioning
confidence: 99%
“…Bjornstad et al [ 16 ] estimated the transmission rates of measles for England and Wales using the tSIR model. Deo and Grover [ 17 ] noticed that the unreported pathogens are more threatening than reported and quarantined ones. Their proposed model was susceptible-infected (quarantined/free)-removed-deceased (SI(Q/F)RD).…”
Section: Introductionmentioning
confidence: 99%